Naturalisation and on-the-job training: Evidence from first-generation immigrants in Germany - Friederike von Haaren-Giebel; Malte Sandner (IZA Journal of Migration, 2016)
This paper empirically analyses the effect of naturalisation on on-the-job training (OJT) participation among first-generation immigrants in Germany. OJT is associated with improved labour market outcomes and provides therefore an indicator for labour market integration. Naturalisation is assumed to act as a signal of the employee's commitment to the host country and may thus increase employers' likelihood of offering OJT. Testing the theoretical link with multivariate estimations (based on the German Socio-Economic Panel) shows a positive and significant correlation. To reduce selection bias on observables, propensity score matching is applied, yielding a significant average treatment effect.
Keywords: J15; J24; M53; 330; Citizenship; Integration; Human capital; SOEP